Endoglucanase production with the newly isolated Myceliophtora sp. i-1d3b in a packed bed solid state fermentor - Zanelato, A. I. [UNESP] (2012)
This work is aimed to produce endoglucanase through solid state fermentation in a packed bed bioreactor with the use of the fungus Myceliophtora sp. I-1D3busing a mixture of wheat bran (WB) and sugar cane bagasse (SCB) as culture medium. Preliminary tests were performed in polypropylene plastic bags, controlling the variables temperature (40, 45, and 50ºC), initial moisture content (75, 80, and 85%, w.b.), and weight proportion SCB/WB (1:1, 7:3, and 9:1). The highest enzyme activities in plastic bags were obtained using the substrate proportion of 7:3, 50ºC temperature, and 80% initial moisture content (878 U/grams of dry solid). High activities of filter-paper cellulase and xylanase were also obtained in plastic bags and some results are reported. For the packed bed experiments, the temperature (45 and 50ºC) and the air flow rate (80, 100 and 120L/h) were the controlled variables. Activity of endoglucanase was similar to plastic bag tests. A longitudinal gradient of moisture content, was observed increasing from the bottom to the top of the reactor, even though the longitudinal enzyme activity profile was flat for almost the whole bed. Air flow rate did not affect enzyme activity, while experiments carried out at 50ºC showed higher enzyme activities. The maximum temperature peak observed was at about 6ºC above the process temperature.